Influence of rotation angle of a triangular tube with a built‐in twisted tape on the thermal‐exergy efficiency and entropy generation of nanofluids in the heat exchange system. Issue 1 (14th January 2020) - Qi, Cong; Li, Chunyang; Zhao, Gongbin; Liu, Maoni; Han, Dongtai
Abstract: In order to investigate the thermal‐exergy efficiency and entropy generation of nanofluids flowing through a triangular tube with a built‐in twisted tape, a heat exchange system is designed and established. Deionized water and three mass concentration nanofluids ( ω = 0.1 wt%, 0.3 wt%, and 0.5 wt%) are applied as the heat‐transfer mediums flowing through three different rotation angle ( α = 0°, 30°, and 60°) triangular tubes, respectively. Thermal efficiency index ( η ) and entropy generation ( S ) are used to characterize the performance of the heat exchange system. It is proved that the increase of nanoparticles can not only effectively promote the heat transfer effect but also augment the pressure loss. Nusselt number of nanofluids is increased by 20.2% on average, whereas the flow resistance coefficient is increased by 10.1% on average. Based on the thermal efficiency index, the data demonstrate that ω = 0.5 wt% nanofluids in the triangular tube at α = 0° can make the most effective use of energy, whose value could reach 1.32 at most. Exergy efficiency of nanofluids in the heat exchange system can be evidently heightened under the same pumping power and flow rate. Entropy production of 0.1 wt% nanofluids is the smallest.